Edukasi Pengobatan Sendiri (Swamedikasi) Siswa/Siswi Sekolah Menengah Kejuruan “Bina Nusa Mandiri” Jakarta Timur - Chusun Chusun; Indrianti Poppy; Nabila Nuha (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Vocational High School students are a group of people who are growing up and need knowledge about self-medication which, if done correctly, can assist the government in improving public health status. Self-medication Education Activities at Vocational High School